(untitled) (Vietnam Journal of Community Medicine, 2024)
Research Objective: To determine the rate of different types of syncope through the tilt table test and to assess the relationship between age and gender with the results of the tilt table test. Study Subjects and Methods: Patients suspected of reflex syncope who were eligible for the tilt table test were included in the study. Patients were classified based on their responses in terms of heart rate and blood pressure, and divided into groups: negative, positive (mixed type, cardioinhibitory type, and vasodepressor type). Results: Out of 95 patients, 5 (5.3%) did not complete the tilt table test. Negative results accounted for 32.6%, while positive results comprised 62.1% (mixed type 30.5%, cardioinhibitory type 6.3%, vasodepressor type 25.3%). There was no correlation between gender or age and the results of the tilt table test. Conclusion: The rate of mixed-type neurocardiogenic syncope was the highest, while the rate of cardioinhibitory type requiring intervention was the lowest. Gender and age were not factors influencing the results of the tilt table test.